Evaluation of Pre-harvest Microbiological Safety of Blueberry Production With or Without Manure-Derived Fertilizer - Shen, Xiaoye; Sheng, Lina; Benedict, Chris; Kruger, Chad E.; Su, Yuan; Schacht, Elizabeth; Zhang, Yifan; Zhu, Mei-Jun (Frontiers in Microbiology, 2020)
Blueberry is an important commodity in the Washington State, which was one of the leading blueberry producers in the US. As a ready-to-eat fruit, blueberry has no or limited post-harvest processing, highlighting an imperative need to evaluate microbial safety during preharvest practice. This study accessed the microbiological safety of blueberry produced in a commercial blueberry field using standard fertilizer (CON) or manure-derived ammonium sulfate (AS) fertilizer in a 2-year field study. AS was either applied once for each production season (AS1) or in a split application four weeks apart (AS2). Indicator microorganisms of total coliforms and generic E. coli, Shiga toxin-producing Escherichia coli (STEC), Salmonella and Listeria monocytogenes were monitored in fertilizer, soil, foliar, and blueberry fruit samples by culture-based isolation and plating methods through each production season. The population of total coliforms in soils were 3.17 - 3.82 Log10 CFU/g, which were stable throughout the production season and similar between two cropping seasons. Generic E. coli in soils remained at very low levels of 0.13-0.25 Log10 CFU/g throughout the production season. Total coliforms or generic E. coli were not detected in fertilizer, foliar and blueberry fruit samples collected in both 2017 and 2018 production seasons. STEC and L. monocytogenes were all below the detection limit in fertilizer, soil, foliar and blueberry fruit samples collected in both production seasons regardless of fertilizer application practices. Salmonella was not detected except for soil samples collected pre- and post-fertilizer application in the 2018 cropping season. Collectively, data indicated, under good agricultural practice, the current blueberry production of using manure-derived AS fertilizer in blueberry field had no negative impact on the microbiological safety of blueberry.